Studi Pemahaman UMKM Atas Pembuatan Laporan Keuangan Berbasis Sak Emkm: UMKM Kecamatan Rumbai Pekanbaru - Yani, Fitri; Syarli, Zikri Aidilla (Jurnal Impresi Indonesia, 2025)
Low accounting literacy among MSMEs is the main obstacle in achieving Indonesia's sustainable economic targets. Although SAK EMKM has come here as a simplified accounting standard solution, its adoption rate is still low. This study aims to determine the understanding of MSMEs in preparing financial reports based on the Indonesian Financial Accounting Standards (SAK EMKM). The research approach used is descriptive. The population in this study were MSMEs engaged in the bread production business in Mandau District, Bengkalis Regency. Data collection methods were conducted through interviews and documentation of eight MSME bread producers in Mandau District, Bengkalis Regency. The data analysis technique used in this study was qualitative descriptive analysis. The results of this study, following the interviews, indicated that MSMEs have recorded their finances, but only in a basic manner. MSMEs' understanding of preparing financial reports based on the Indonesian Financial Accounting Standards (SAK EMKM) remains low. The financial reports produced by MSMEs are still far from compliant with the Indonesian Financial Accounting Standards (SAK EMKM). This study emphasizes the importance of education and mentoring for MSMEs to improve their understanding of the obligation to prepare financial reports in accordance with the Indonesian Financial Accounting Standards (SAK EMKM). With this increased understanding, it is hoped that compliance and the quality of MSME financial records can be improved to support sustainable economic growth.